Intrahousehold Bargaining, Female Autonomy, and Labor Supply: Theory and Evidence from India. Issue 4 (22nd July 2019) - Heath, Rachel; Tan, Xu
Abstract: Standard models of labor supply predict that unearned income decreases labor supply. We propose an alternative noncooperative household model in which a woman's unearned income improves her autonomy within the household, which raises her gains from working and can increase her labor supply. We find empirical support for this model, using women's exposure to the Hindu Succession Act in India as a source of exogenous variation in their unearned income. Exposure to the Hindu Succession Act increases a woman's labor supply by between 3.8 and 6.1 percentage points, particularly into high-paying jobs. Autonomy increased by 0.17 standard deviations, suggesting that control of income is a potential channel for these effects. Thus, policies that empower women can have an additional impact on the labor market, which can further reinforce autonomy increases.